Microbiological analyses and students’ attitudes and perceptions towards microbiological risks of plant-based meat items - Chong, Careen Kai Lyn (2023)
Plant-based meat was created to taste, feel, and look like traditional animal meat. It can improve health and reduce the risks of chronic illnesses. In recent years, consumers toward veganism kept increasing and the popularity of plant-based meat products has grown steadily in global market trends. These newly emerging food products were important to be microbiologically investigated, and the consumers’ attitudes and perceptions of microbiological risks of plant-based meat were also important for food safety purposes. This study aims to determine the microbiological quality of plant-based meat items in relation to the attitude and perception towards microbiological risks of plant-based meat items among Universiti Tunku Abdul Rahman (UTAR), Kampar students. Aerobic colony count (ACC) and yeast and mold count (YMC) were determined in three plant-based meat meal samples. Collected data were analyzed using SPSS to generate research findings. Questionnaires were distributed to 165 UTAR Kampar students to determine the level of attitude and perception towards microbiological risks on plant-based meat items. Collected data were analyzed by Microsoft Excel to obtain research findings. A significant increase iii was found in the microbial counts of all food samples as time storage is prolonged at room temperature (25±2°C). In contrast, no significant difference (p > 0.05) was found in the microbial loads of all food samples stored for 2 days at refrigeration temperature (4±2°C). A significant difference (p < 0.05) was found for the avocado charcoal bun’s microbial loads stored for 24 hours at room and refrigeration temperatures. Positive attitudes and perceptions were seen in most respondents toward the microbiological risks of plant-based meat items. These results concluded that microbial counts could differ depending on the specific food item and storage conditions. The survey concluded that students were aware of the microbiological risks of plant-based meat items